Stylistic and Linguistic Characteristics of "The Memoirs" by Milan Petrović - Ivanović, Janko R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper highlights and describes the characteristic linguistic and stylistic features of Milan Petrović’s memoirs. The aim of the paper is to single out and describe the basic linguistic and stylistic features of the language by applying grammatical and linguistic criteria and methods. Given that it is a memoir, we tried to determine whether elements of a literary-artistic or scientific functional style prevail in the book. Eight memoir texts by this author are included in the analysis.The conducted analysis of Milan Petrović’s style and language in his book suggests several important conclusions. His style is simple, the sentence is narrative, never structurally complicated, with a small number of clauses in its composition. It is an essayistic-scientific style, with many literary touches, with conscious literaryization, carried out with the aim of achieving greater beauty of the language. In addition to all this, in the language of Milan Petrović we also find purely scientific linguistic features, such as decomposed predicates, the frequent use of adverbs, as well as the author’s ‘we’, as well as many historical facts.As for the grammatical features, his language does not differ much from the modern Serbian language. Given that Milan Petrović lived and worked in the area of the Šumadija-Vojvodina dialect, which became the basis of the Serbian literary language, there are very few deviations from the norm in his language. On the other hand, the narration, as well as all the linguistic features underlying these Petrović memoirs, represent their most immanent characteristic. That is why we cannot view his memoirs exclusively as a scientific-historical text, but as a literary text, which also contains certain scientific elements.
Keywords: Milan Petrović; memoirs; linguistic style; literary style; scientific style